Development of microfluidic device for cell lysis - Maraschin, Samuel Tavares da Silva (Universidade do Vale do Rio dos Sinos, 2021)
The use of certain protocols to diagnose diseases requires specific tools and highly qualified professionals. This high-end scenario has leveraged the development of new mechanisms and processes on biomolecular analyses. In this context, recent discussions regarding new portable and low-cost devices which enable faster results have been receiving attention due to the possibility of speeding up physician decision making. The speed of decision-making has garnered attention even prior to the 2020 pandemic, and has proved to be an important factor in successful treatments. The process of disrupting cell membrane is known as cell lysis. This process is a fundamental step in several molecular analyses such as Polymerase Chain Reaction (PCR) standard analysis to diagnose diseases such as Sars CoV 2 (COVID-19) and many others. The standard protocol to perform PCR uses specific chemicals to rupture cell membrane, which increases the costs of tests. Since these materials are not currently available in the Brazilian market, it results in a long lead time. In addition, the protocols used to run PCR require specific training for staff, adding extra cost and time into the process. Therefore, this study presents the development of a microdevice for cell lysis. The proposed device was made using microfabrication techniques developed by the microelectronics industry. The microdevices have shown some advantages to conventional technologies such as portability, faster results, and a decrease of contamination risk when the samples are handled in a closed system. To prove the efficiency of the device, two analyses were performed: RNA concentration measured by a spectrophotometer and amplification of genetic material using PCR methodology. Based on results obtained through this technology, it was possible to establish the great prospective brought out by this method on health services reducing cost and speeding up results. A microdevice with 15 μm electrodes got promising results when compared to the ones from standard techniques. A significant time reduction on sample preparation, aside from portability and friendly user operation are some of benefits provide by the proposed device.
Keywords: Lise celular; Diagnóstico; Microfabricação; Amplificação RNA; Cell lysis; Diagnostic; Microfabrication; DNA amplification; ACCNPQ::Engenharias::Engenharia Elétrica